Influences of Adult Gender and Parenthood on Adult-Child Interaction Style - Darcy K. Smith; Ran An; Klaus Libertus (MDPI AG, 2022)
Previous studies report differences between mothers and fathers during parent-child interactions. However, the origins of these differences remain unknown. We address this gap by examining the impact of adult gender and gender perceptions on adult-child interactions. Unlike previous studies, we observed both parent and non-parent adults during one-on-one interactions with a child. Further, for non-parent adults the child's identity was held constant while the child's assumed gender was actively manipulated using clothing cues. Results reveal systematic differences between parents and non-parents, but also between male and female adults in language quantity, quality, and engagement strategies during adult-child interactions. Adults' perceptions of gender roles partially explain these findings. In contrast, the child's gender did not impact adult-child interactions. Together, our results support the notion that male and female adults offer unique contributions to a child's development.